Prevalence of Mismatch Repair Deficiency in Primary Prostate Cancer in a Large Prospective Cohort - Baird, Anne-Marie; Cadoo, Karen; Barr, Martin; Finn, Stephen; Gray, Steven; Sheils, Orla (AACRJournals.org, 2025)
Background: Mismatch repair (MMR) deficiency and microsatellite instability are predictive biomarkers for immunotherapy response. The best approach to identify patients with such tumors is unclear in prostate cancer. Methods: This study included 1,016 men diagnosed with primary prostate cancer during prospective follow-up of the Health Professionals Follow-up Study and Physicians’ Health Study. Highest-grade/index lesions from radical prostatectomy (95%) or transurethral resections of the prostate were mounted on tissue microarrays. Scoring of immunohistochemistry for the MMR proteins MLH1, MSH2, MSH6, and PMS2 required a non-tumor internal positive control for designating deficiency. Validation was done on full sections and with PCR-based quantification of microsatellite repeats. Results: Tumor stage was predominantly pathologically localized with a full distribution of Gleason scores. MMR tumor scoring could be performed with available internal positive control tissue in 75%–90% of cases, depending on the MMR protein. Of the 903 tumors evaluable for MSH2 protein loss, 4 tumors had loss of MSH2 (prevalence 0.4%, 95% confidence interval [CI] 0.2–1.1%), and 3 of 708 evaluable tumors had concomitant loss of MSH6 (prevalence 0.4%, 95% CI 0.1–1.2%). No tumor had loss of MLH1 or PMS2. The 4 MMR-deficient cases had higher Gleason scores, and 3 had non-zero microsatellite repeats. Conclusions: In this nationwide prospective study, MMR deficiency was rare in primary, surgically treated prostate cancer. The low prevalence and the need for an internal positive control for this assay are feasibility concerns for unselected routine immunohistochemistry-based screening for MMR deficiency on limited tissue specimens, such as prostate biopsies.
PUBLISHED
Keywords: mismatch repair; prostate cancer; immunohistochemistry; prevalence; Cancer; Lynch Syndrome; MICROSATELLITE INSTABILITY; MLH1; MSH2; MSH6; PMS2; Tissue microarray